High-performance computing and concurrency : understanding hardware-software interactions and how to speed up your programs - Pikus, Fedor G. (O'Reilly, 2016)
"It's deja vu all over again. In the old days (35 plus years ago), developers wanting to write half-decent programs had to know their hardware. Those days are back. Clock frequencies have peaked and hardware can no longer be abstracted behind high-level languages. Designed for developers with high performance requirements (games, finance analysis, scientific computation, etc.), this course teaches you what really happens when programs are executed and the subtle details that make a program go slow or fast. With a focus on concurrency, specifically local concurrency (multi-threading), the course is all about writing efficient programs that make the best use of the computing resources available to you. While the sample code is written in C++, the course is not C++ specific. If you can read C++ code, but don't use it in your work, you will still learn from this class."--Resource description page.